1994
DOI: 10.1113/jphysiol.1994.sp020136
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo study of the effects of ischaemia on uterine contraction, intracellular pH and metabolites in the rat.

Abstract: 1. There are no data concerning the functional or metabolic effects of hypoxia in vivo in smooth muscle. We have therefore used 3"P-NMR spectroscopy and intra-uterine pressure measurements to examine simultaneously, in vivo, the effect of ischaemia on uterine metabolites, intracellular pH (pHi) and force.2. A 1-2 cm portion of uterus from day 1 postpartum anaesthetized rats was exteriorized and an NMR surface coil placed on it. A balloon catheter in the uterine lumen recorded intra-uterine pressure changes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 13 publications
5
41
1
Order By: Relevance
“…An increase of force (intrauterine pressure) of 130-140% on reperfusion was reported and lasted for over 30 min. The significance of these data were not appreciated at the time (4,12). Our protocols (and in vivo studies) were developed to clearly demonstrate the effects of repetitive hypoxia and investigate its mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of force (intrauterine pressure) of 130-140% on reperfusion was reported and lasted for over 30 min. The significance of these data were not appreciated at the time (4,12). Our protocols (and in vivo studies) were developed to clearly demonstrate the effects of repetitive hypoxia and investigate its mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This is known as hypoxic or ischemic preconditioning, and has been best investigated in cardiac muscle (10) and brain (11), where it is considered to be a powerful mechanism for limiting ischemic damage. Given that physiological decreases in oxygenation are part of the normal process of labor (4,12), this finding therefore raised some important questions: What is the effect of brief but repetitive periods of hypoxia on uterine contractility? And, do cycles of brief hypoxia initiate and maintain the progressive augmentation of contractility needed for labor?…”
mentioning
confidence: 99%
“…The finding that MLC20 phosphorylation levels in tissues depolarized in the absence or presence of agonists were unaffected by cyanide treatment indicates that [ATP] surrounding the myofilaments remained sufficient to support contractile activity (see below) since, under physiological conditions, MLC20 dephosphorylation precedes relaxation (Khromov, Somlyo, Trentham, Zimmermann & Somlyo, 1995 (Wray, 1990). Similarly, in vivo occlusion of the uterine artery of anaesthetized rats resulted in abolition of contractile activity accompanied by only moderate decreases in [ATP] and [phosphocreatine] (Harrison et al 1994). This is in agreement with Hardin, Wiseman & Kushmeric (1992) who suggested that isometric force generation of hypoxic vascular smooth muscle was not limited by the [ATP].…”
Section: Mlc20 Phosphorylation During Inhibition Of Oxidative Phosphomentioning
confidence: 93%
“…By the CPT theorem, in vacuum, observation of T-violation is identical to observation of CP-violation. Even in a terrestrial oscillation experiment, since a possible T-odd effect from asymmetric matter density profile in the earth is very small [12], this T-reversed difference reveals as a very clean signal [2,13] on the imaginary phase in the lepton sector [2,9,10,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%